2014
DOI: 10.1080/08959420.2014.854142
|View full text |Cite
|
Sign up to set email alerts
|

Building an Integrated Research/Policy Planning Age-Friendly Agenda

Abstract: This article describes an innovative model for integrating research into a policy and planning agenda aimed to help neighborhoods become more supportive of older adults. Philadelphia Corporation for Aging (PCA) established Age-Friendly Philadelphia (AFP) to catalyze efforts to improve the physical and social environments for seniors. The Research Program at PCA became an important part of this effort by providing multiple types of supports to PCA staff and other stakeholders. Most notably, the research program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…This notion is supported by research findings that professionally facilitated community development with and by older adults in the neighbourhood can result in more hospitable and supportive community environments for older people by increasing civic engagement and social capital (Austin et al 2005;Buffel et al 2012a). Several recent case studies of age-friendly communities (Buffel et al 2014;Glicksman et al 2013;, as well as an evaluation of European Healthy Cities (Green et al 2015), have also elucidated policy and governance factors that are conducive to age-friendly communities.…”
Section: Urbanization and Population Ageingmentioning
confidence: 55%
“…This notion is supported by research findings that professionally facilitated community development with and by older adults in the neighbourhood can result in more hospitable and supportive community environments for older people by increasing civic engagement and social capital (Austin et al 2005;Buffel et al 2012a). Several recent case studies of age-friendly communities (Buffel et al 2014;Glicksman et al 2013;, as well as an evaluation of European Healthy Cities (Green et al 2015), have also elucidated policy and governance factors that are conducive to age-friendly communities.…”
Section: Urbanization and Population Ageingmentioning
confidence: 55%
“…An examination of some of the literature emanating from the Aging Friendly environments movement raises similar issues (e.g. Glicksman et al, 2014), including neighborhood crime or the need for civic and social engagement. However, to truly estimate the impact of those factors, new quantitative studies need to examine the relative contribution of these variables to loneliness within different communities.…”
Section: Discussionmentioning
confidence: 99%
“…These four studies highlighted the contribution that effective partnerships can make to implementing agefriendly initiatives. In support of this, Glickman et al (2014) suggested research can be successfully integrated into policy and planning for age-friendly communities. The perceptions, participation and contributions of older people in implementing age-friendly initiatives have been widely asserted and were evident in the studies reviewed (Lui et al 2009, Plouffe & Kalache 2011, Buffel et al 2012, Novek & Menec 2014.…”
Section: Discussionmentioning
confidence: 83%